2011
DOI: 10.1364/oe.19.017462
|View full text |Cite
|
Sign up to set email alerts
|

Optical trapping through the localized surface-plasmon resonance of engineered gold nanoblock pairs

Abstract: Abstract:We have investigated the plasmonic trapping of dielectric nanoparticles by using engineered gold nanoblock pairs with ~5-nm gaps. Pairs with surface-plasmon resonance peaks at the incident wavelength allow the trapping of 350-nm-diameter nanoparticles with 200 W/cm 2 laser intensities, and their plasmon resonance properties and trapping performance are drastically modified by varying the nanoblock size of ~20%. In addition, plasmon resonance properties of nanoblock pairs strongly depend on the directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 26 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…Additionally, several plasmonic patterns, which are tunable, have been demonstrated to dynamically trap particles, and some of these novel geometries are summarized in this sub-section. Particularly, Tanaka et al [102,149] studied theoretically and experimentally the strong trapping potential which can be formed using gold nanoblock pairs. They demonstrated that the size and orientation of the pairs of gold nanoblocks, with 5 nm gaps, determine their surface-plasmon resonance properties and trapping performance in conjunction with the wavelength and the polarization direction of the incident laser [102].…”
Section: Pot With Alternative Nanostructure Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several plasmonic patterns, which are tunable, have been demonstrated to dynamically trap particles, and some of these novel geometries are summarized in this sub-section. Particularly, Tanaka et al [102,149] studied theoretically and experimentally the strong trapping potential which can be formed using gold nanoblock pairs. They demonstrated that the size and orientation of the pairs of gold nanoblocks, with 5 nm gaps, determine their surface-plasmon resonance properties and trapping performance in conjunction with the wavelength and the polarization direction of the incident laser [102].…”
Section: Pot With Alternative Nanostructure Geometriesmentioning
confidence: 99%
“…They demonstrated that the size and orientation of the pairs of gold nanoblocks, with 5 nm gaps, determine their surface-plasmon resonance properties and trapping performance in conjunction with the wavelength and the polarization direction of the incident laser [102]. Moreover, they demonstrated optical trapping of 350 nm polystyrene particles with 750 W/cm 2 laser intensities [102]. Similarly, 2 years later, they performed two-dimensional mapping of the optical trapping of 100 nm fluorescent polystyrene particles above a gold nanoblock pair that had a 6 nm edge-to-edge separation [149].…”
Section: Pot With Alternative Nanostructure Geometriesmentioning
confidence: 99%
“…The authors showed that the particle's [115] 2013, Nano Lett.) [117] 2011, Opt. Express) motion always served to create a force that pushed the particle back to its equilibrium position.…”
Section: Self-induced Back Actionmentioning
confidence: 99%
“…Localized surface plasmons can be used for enhanced trapping well below the diffraction limit. Tanaka et al referred to this ability as superresolution optical trapping [117]. Their plasmonic structure consisted of only two square gold nanoblocks, as shown in Fig.…”
Section: Superresolution Optical Trappingmentioning
confidence: 99%
“…[2][3][4][5] This drawback can be overcome with plasmonic nanoapertures in metallic films [6,7] and planar waveguides [8] where the nanostructures can produce a giant near-field gradient in the subwavelength area, [9] enabling precise trapping, manipulation, and characterization of nanoparticles. For example, plasmonic nanostructures such as nanorods, [17] nanorings, [18] antennae, [19] and coaxial apertures [20] have a well-defined trapping site in the gap region between the resonators and are capable of trapping molecules a few tens of nanometers in size. The LSPR modes are characterized by exponential decay of the EM fields DOI: 10.1002/adts.201700027 away from the interface of the metal and dielectric.…”
Section: Introductionmentioning
confidence: 99%